MECHANISM IMPLEMENTATION OF CORPORATE SOCIAL RESPONSIBILITY BY THE MINING COMPANY - Dewantara, Reka (Wisesa: Jurnal Pengabdian Masyarakat, 2022)
The ratification of UUPT No. 40 of 2007 is an urgent need for entrepreneurs as entrepreneurs and the state as a regulator of commercial life. This is because the GmbH law that was in effect before is no longer relevant to the development of business life. In general, there have been several significant substantive changes to the Limited Liability Company Law, one of which is the Corporate Social Responsibility (CSR) or Law no. 40 of 2007 which expresses the notion of social and environmental responsibility. The method used in this research is empirical juridical by using descriptive qualitative data analysis method. The results of this community service show that improving the company's performance at the KPC mine can be increased by carrying out its CSR program, therefore the company and the CSR team within it must approach the local community who are located around the mining area more frequently. The approach to the community is carried out by cooperating with academics, this aims to identify the economic, social, environmental, and cultural backgrounds of the community, then ensures the achievement of the expected impact with limited resources the company also holds various pieces of training for the community, this approach is taken to prevent community disputes when participating with the company.